Rectal Cancer and Radiation in Colitis - Lynn, Patricio B.; Cronin, Catherine; Rangarajan, Sriram; Widmar, Maria (Clinics in Colon and Rectal Surgery, 2023)
Inflammatory bowel disease (IBD) is associated with an increased risk of colorectal cancer. When IBD patients develop a rectal cancer, this should be treated with the same oncological principles and guidelines as the general population. Rectal cancer treatment includes surgery, chemotherapy, and radiation therapy (RT). Many IBD patients will require a total proctocolectomy with an ileal-pouch anal anastomosis (IPAA) and others, restoration of intestinal continuity may not be feasible or advisable. The literature is scarce regarding outcomes of IPAA after RT. In the present review, we will summarize the evidence regarding RT toxicity in IBD patients and review surgical strategies and outcomes of IPAA after RT.
Keywords: inflammatory bowel disease; rectal cancer; ileal pouch-anal anastomosis; radiation therapy; functional outcomes